2019
DOI: 10.30871/jaat.v4i2.1081
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Perceived Ease of Use, Perceived Usefulness and Consumer Satisfaction Towards Online Purchasing Behavior

Abstract: This study aims to examine the effect of perceived ease of use, perceived usefulness and consumer satisfaction on online purchasing behavior. This study used 200 respondents taken from the general public living in the area of Batam. The type of data used in this study is the interval scale. Scaling method used in the instrument of Likert scale with 5 rating categories. Data processing techniques in this study using software program SPSS 17. The results of this study indicate that the variables perceived ease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(2 reference statements)
1
1
0
Order By: Relevance
“…Another finding that emerged as a result of the analysis is that perceived ease of use indirectly affects purchase behavior. The results of similar studies in the literature also support this finding (AlSaleh, 2017;Syakir and Setiyanto, 2019). In addition, the admiration variable also has an indirect effect on purchase behavior.…”
Section: Discussionsupporting
confidence: 67%
“…Another finding that emerged as a result of the analysis is that perceived ease of use indirectly affects purchase behavior. The results of similar studies in the literature also support this finding (AlSaleh, 2017;Syakir and Setiyanto, 2019). In addition, the admiration variable also has an indirect effect on purchase behavior.…”
Section: Discussionsupporting
confidence: 67%
“…This ease of use is crucial for achieving desired outcomes. The study by Setiyanto and Syakir (2019) examined the impact of perceived ease of use, usefulness, and consumer satisfaction on online purchasing behavior among 200 Batam-based public respondents using an interval and Likert scale with 5 rating categories. Results showed that these factors partially influence online purchasing behavior.…”
Section: Review Of Literaturementioning
confidence: 99%